Employing brand governance mechanisms with export channel partners: What are the performance consequences and contingent effects?. Issue 5 (October 2022) - Pyper, Keith; Doherty, Anne Marie
Abstract: For decades leading international business scholars have assessed the benefits accruing from successful governance mechanisms. Although the critical importance of initiating and maintaining good relationships with export channel partners is recognized within the literature, there has been little research focus placed on the optimal approach for governing intangible aspects of these relationships. We offer the first integrated definition of export brand governance of channel partners (EBGoCP) and investigate its influence on export performance. Drawing from relational governance theory and contingency theory, we develop and test a model of the contingent effects of different country specific advantages and firm characteristics on the performance upshots of EBGoCP. Using survey data from UK exporters, our findings validate the hypothesized enhancing effects of EBGoCP on export performance outcomes. Furthermore, consistent with our contingency based predictions, we find country-of-origin-image, firm size and scope of exporting moderate the impact of EBGoCP on export performance. Along with providing fresh insights from the results, this study opens up a new stream of international business governance research and offers productive future research paths to follow. Highlights: Export Brand Governance of Channel Partners (EBGoCP) is important for IB. There is a positive link between EBGoCP and export performance. COI, firm size and scope of exporting moderate the EBGoCP – export performance link. Relational governance mechanisms are effective for knowledge based brand assets. COI can strongly influence brand attitudes for B2B export channel partners.